Generasi Z di Era Politik Digital: Bagaimana Media Sosial Membentuk Kecemasan dan Antusiasme dalam Pilkada Bogor 2024 - Herwanto, Dony Putro; Febrianti, Dwika (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
With Generation Z's increasing reliance on digital platforms for information, social media has become an important battleground in shaping their political attitudes and behaviours. Political content that is freely spread on social media under the pretext of political education or personal branding, often influences anxiety which ultimately gives birth to apathy, although on the one hand, it can create high enthusiasm among Generation Z as novice voters in the democratic party. The purpose of the study was to determine the extent to which social media platforms affect the anxiety and enthusiasm of generation Z, and how interaction with political content on social media can affect generation Z's perceptions and attitudes towards elections. This research uses quantitative methods to collect data from first-time voters who are active on social media. The results show that political content disseminated through social media can increase anxiety among Generation Z, especially when the information received is negative or frightening. On the other hand, positive campaigns and calls to participate in elections through these platforms can increase their enthusiasm to vote. The conclusion of this study emphasises that social media has a significant impact in influencing Generation Z's political emotions.